Tumors and Related Lesions of the Pigmented Epithelium. Issue 2 (March 2017) - Shields, Jerry A.; Shields, Carol L.
Abstract : Abstract: : Several tumors and pseudotumors can arise from the iris pigment epithelium (IPE), ciliary pigment epithelium (CPE), and retinal pigment epithelium (RPE), including cysts of the IPE, solitary congenital hypertrophy of the RPE (CHRPE), multifocal CHRPE ("bear tracks"), congenital simple hamartoma of the RPE, combined hamartoma of the retina and RPE, and acquired epithelioma of IPE, CPE, and RPE. This article describes examples of pigment epithelial tumors and pseudotumors by reviewing the literature and cases on file in the Oncology Service at Wills Eye Hospital. Solitary CHRPE, traditionally believed to be stationary, can show growth in diameter in 83% and can spawn elevated nodular tumors that can progressively enlarge, cause complications, and even evolve into malignant epithelioma (adenocarcinoma). Multifocal CHRPE (congenital grouped pigmentation) has no relationship to familial adenomatous polyposis or Gardner syndrome, despite its similarity to the pigmented fundus lesions seen with those conditions. Congenital simple hamartoma of the RPE is a specific lesion that involves the fovea and does not tend to cause complications. Combined hamartoma, an idiopathic proliferation of RPE cells, blood vessels, and glial cells, is also believed to be a relatively stable lesion but can cause vision loss due to traction. Acquired tumors (adenoma, adenocarcinoma) have features distinct from melanoma clinically and histopathologically. Torpedo maculopathy is a small stable lesion with typical features, resembling a torpedo. There are several intriguing tumors and pseudotumors of the pigmented epithelium that have major clinical and histopathologic importance.